Effect of Rifampicin on The Pharmacokinetics of Selexipag, An Oral Prostacyclin Receptor Agonist, and Its Active Metabolite In Healthy Male Subjects - Bruderer, S.; Petersen-Sylla, M.; Boehler, M.; Remeňová, T.; Halabi, A.; Dingemanse, J. (Clinical therapeutics, 2017)
Methods This was an open-label, randomized, two-treatment, two-period, crossover study including 20 healthy male subjects. Concomitant administration of selexipag and multiple-dose rifampicin led to no relevant change in exposure to selexipag (geometric mean ratios [Treatment B/Treatment A] and 90% confidence intervals [CIs] for maximum plasma concentration (Cmax) and area under...